The Effect of Transformational Leadership and Organizational Culture on Employee Performance at PT Wijaya Gyokai Indonesia - Muhammad Chumaedi; Lisa Harry Sulistiyowati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the effects of transformational leadership and organizational culture on employee performance at PT Wijaya Gyokai Indonesia. A quantitative research design with a survey approach was employed. The sample comprised 80 respondents selected using the Slovin formula. Data were collected through structured questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that transformational leadership does not have a positive and insignificant effect on employee performance, whereas organizational culture has a positive and significant effect on employee performance. Simultaneously, transformational leadership and organizational culture significantly influence employee performance. The coefficient of determination shows that the two independent variables explain 43.8% of the variance in employee performance. These findings suggest that strengthening organizational culture plays a crucial role in enhancing employee performance, particularly in manufacturing companies.